2023
DOI: 10.3390/jof9030343
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Edible Amanita in Northern Thailand and Their Nutritional Value, Total Phenolic Content, Antioxidant and α-Glucosidase Inhibitory Activities

Abstract: Edible wild mushrooms are extremely popular among consumers and are highly valued for their potential economic benefits in northern Thailand. In this present study, a total of 19 specimens of edible Amanita were collected during investigations of wild edible mushrooms in northern Thailand during the period from 2019 to 2022. Their morphological characteristics and the phylogenetic analyses of the internal transcribed spacer (ITS) and partial large subunit (nrLSU) of ribosomal RNA, RNA polymerase II second-larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…In this study, the ethanolic extract of P. sribuabanensis specimen CMUNK0930 exhibited the highest degree of antioxidant activity due to its high total phenolic content. This finding was supported by those of previous studies that demonstrated that the high levels of phenolic content are responsible for the high antioxidant activity [ 11 , 46 , 69 , 71 , 76 ]. According to Pearson correlation ( p < 0.05), the total phenolic content of the ethanolic extracts of P. sribuabanensis showed a significantly strong positive correlation with ABTS ( r = 0.998, p = 0.03) and DPPH ( r = 0.999, p = 0.01) activities.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the ethanolic extract of P. sribuabanensis specimen CMUNK0930 exhibited the highest degree of antioxidant activity due to its high total phenolic content. This finding was supported by those of previous studies that demonstrated that the high levels of phenolic content are responsible for the high antioxidant activity [ 11 , 46 , 69 , 71 , 76 ]. According to Pearson correlation ( p < 0.05), the total phenolic content of the ethanolic extracts of P. sribuabanensis showed a significantly strong positive correlation with ABTS ( r = 0.998, p = 0.03) and DPPH ( r = 0.999, p = 0.01) activities.…”
Section: Resultssupporting
confidence: 87%
“…Local farmers have collected them in forests for general consumption and sell them at localized, roadside, and urban markets [ 10–12 ]. According to preliminary investigations conducted in northern Thailand, numerous genera of edible wild mushrooms have been reported, including Agaricus , Amanita , Astraeus , Boletus , Cantharellus , Lactarius , Lentinus , Panus , Pleurotus , Russula , and Termitomyces [ 11–13 ]. However, Thai edible wild mushrooms have not yet been well studied and documented.…”
Section: Introductionmentioning
confidence: 99%
“…& Broome) Sacc., A. malayensis, A. kitamagotake N. Endo & A. Yamada, A. rubromarginata and A. javanica. Amanita hemibapha differs by having a darker red pileus centre, an orange margin and narrower spores (5.5-6.5 µm) (Vrinda et al 2005;Cui et al 2018) to more yellowish pileus margin and spore width of 5.5-7 µm (Kumla et al 2023). Amanita rubromarginata and A. javanica differ by having longer pileal striation (0.4-0.5 R) and reddish lamellae edges; A. kitamagotake differs by having uniformly yellow colours on pileus and stipe surface (Yang 2015; Endo et al 2017; Cui et al 2018)d malayensis differs by having a whitishcream stipe and an association with dipterocarps (Tang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the extracts of the other mushrooms showed moderate inhibitory activity against these enzymes (Figure 8b,c). A previous study revealed that the organic extracts of Amanita hemibapha, A. hemibapha, A. pseudoprinceps, and A. subhemibapha (consumed in Thailand) produced 20 to 30% inhibition on AG [34]. The conversion of the IC 50 obtained for the seven edible mushrooms consumed in the NHP revealed that they can inhibit 50 to 70% AG activity.…”
Section: Inhibitory Activity On Key Enzymesmentioning
confidence: 92%